The Effect of Job Insecurity and Workload on Employee Turnover Intantion Study of Bumdes in Jepara Village - Pratama, Ferdi Yoga; Puji, Kemala (Universitas Pamulang, 2025)
This study aims to test and prove the influence of promotions and prices on the satisfaction of purchasing fashion products on Shopee. The population in this study is 524 students of the Faculty of Economics,Universitas teknokrat Indonesia, Management Study Program. This study used a sample of 83 respondents. The research method used is nonprobability sampling with purposive sampling technique. The results of the study showed that the relationship between the independent variable, namely promotion and price, to the independent variable, namely purchase satisfaction. From partial testing, the T test shows that promotion has a positive and significant effect on purchase satisfaction. And on the price variable, it is obtained by proving that price has a positive and significant effect on purchase satisfaction. It can be concluded that promotion and price variables have a positive and significant effect on purchase satisfaction. The Coefficient of Determination (R Square) of 0.535 purchase satisfaction can be explained by promotion and price of 53.5% while the other 46.5% can be explained by other factors that were not examined in this study.